Quick sulfide buffering in inner shelf sediments of the East China Sea impacted by eutrophication - Liu, Juan; Zhu, Mao-Xu; Yang, Gui-Peng; Shi, Xiao-Ning; Yang, Ru-Jun (Environmental earth sciences, 2014)
In the eutrophic coastal ocean, quick formation of iron (Fe) sulfide is environmentally important to effectively prevent accumulation of dissolved sulfide and its detrimental effects on the benthic ecosystem. In this study, 0.5 N HCl-extractable labile Fe (LFe), acid volatile sulfide, and pyrite in the East China Sea inner shelf sediments were examined to investigate the mechanisms of quick sequestration of dissolved sulfide and potential impacts of frequent algal blooms on the capacity of quick sulfide-buffering in eutrophic coastal areas of the large-sized continental shelf subject to massive terrestrial input. The results indicate that sulfate reduction has been competitively suppressed by dissimilatory Fe reduction due to limited availability of labile organic matter. Dissolved sulfide can be quickly buffered by reaction with LFe and, therefore, is difficult to accumulate to a high level. The quick sulfide-buffering capacity has not become exhausted partly because of the formation of un-sulfidized LFe(II) via dissimilatory reduction of less reactive Fe oxides. It is expected that dissolved sulfide will not pose detrimental effects on the benthic ecosystem in the near future if the current biogeochemical/ecological state remains.